Visualising intercity mobility patterns during China’s Spring Festival travel rush under the COVID-19 pandemic - Hengyu Gu; Yuting Zhang (Regional Studies, Regional Science)
This paper introduces a new tool, the lunar phase visualisation, and conducts a multitemporal analysis of the spatial patterns and their changes in China’s intercity mobility during the Spring Festival travel rush between 2019 and 2023. By associating the volume of intercity movement in China across various years with lunar phases, it illustrates that during both the return home (first 20 days) and back-to-city (last 20 days) periods, intercity mobility demonstrates a trend of initial decline followed by an increase. This trend aligns with the onset and subsequent mitigation of the COVID-19 pandemic, with more pronounced changes observed at the city level versus the provincial level. It also underscores the resilience of mobility during traditional holidays amid a public health crisis.